Effect of microcrystalline cellulose on geopolymer and Portland cement pastes mechanical performance. (21st June 2021) - Rocha Ferreira, Saulo; Ukrainczyk, Neven; Defáveri do Carmo e Silva, Keoma; Eduardo Silva, Luiz; Koenders, Eduardo
Abstract: Geopolymers are presented as a new developing construction material and a potential alternative to ordinary binders, but there is a lack of data about several of their properties and behavior – joint-effect with cellulose is one example. The present study investigated the influence of Microcrystalline Cellulose (MCC) addition on the mechanical and microstructural properties of Portland cement and geopolymer pastes. The use of MCC increases compressive strength and stiffness at 7 days to both studied binders. After 28 days, the mechanical properties of the geopolymer paste are reduced due to MCC degradation. On the other hand, MCC addition accelerated geopolymer setting time by 15%, whereas on the cement paste yield a considerable delay effect.